Efficacy analysis using Pabon Lasso Model and comparing with national standards of educational hospitals affiliate to Qom University of Medical Sciences - Abolfazli Mohammadbeig; Zohreh Anbari; maryam hemmati; ahmad rahbar; narges mohammad salehi; fariba eslami moghaddam (Tehran University of Medical Sciences, 2015)
Background: The Pabon Lasso graphical Model is a method to determine hospital efficacy as one of the most important part of health system in developing countries. This study aimed  at assessing the efficacy analysis using Pabon Lasso Model and comparing with national standards of educational hospitals affiliate to Qom University of Medical Sciences. Materials and Methods: This descriptive study conducted in educational hospitals of Qom University of Medical  Sciences in 2011 - 2013. Data collected by approved forms of Health Ministry and three indicators including bed occupancy percentage, bed turnover rate, and average length of Stay were calculated for each hospital using Pabon Lasso model. One sample t-test conducted to data analysis. Results: The mean of bed occupancy and bed turnover was 76.9±9.8 and 100.6±35.4 respectively which were significantly higher than national standards. In addition, the average length of Stay was 3±1.1 days that were similar to standard. The Highest efficacy calculated for IZ hospital and lowest efficacy observed in KA and NE hospitals. Moreover, ZA Hospital can achieve excellent efficacy in 2013. Conclusion: The mean of bed occupancy and bed turnover assessed  very desirable  and higher than national standards. Moreover, only IZ and ZA hospitals had excellent efficacy based on Pabon Lasso model.